A Simple Strategy of Controlling a Balanced Voltage Capacitor in Single Phase Five-Level Inverter - Leonardus Heru Pratomo; F. Danang Wijaya; Eka Firmansyah (Institute of Advanced Engineering and Science, 2015)
The five-level inverter has been used for many applications in renewable energy systems. Even though its harmonic distortion was lower than the conventional two-level inverter. The five-level converter has some disadvantages such as increasing power semiconductor, complex pulse width modulation control methods, and problem with the voltage balancing of the capacitor. This paper aims to propose a modified five-level inverter based on sinusoidal pulse width modulation using phase shifted carrier to enhancing the capacitor voltage balancing. This modified five-level inverter reduces the overall cost and the complexity of the pulse width modulator. Thus making the proposed control system highly simple. The performance and its controller were validated by means of standard laboratory equipments. The analysis, simulation and implementation result showed better performance of five-level inverter.